Implementasi Sistem Informasi Administrasi Dalam Peningkatan Pelayanan Kesehatan Pada Puskesmas Bayan - M. Taufik Rachman; Nidya Putri Syahida; Yana Isnaini (Universitas Muhammadiyah Mataram, 2018)
Health center of Bayan is one of the main health center is location in the north of Lombok district. As the performance of systems running in patient care in the health center of Bayan is still not optimal for the data processing is still done use media bookkeeping. Many of the constraints experienced by the health center, including an error in the input, data storage, and can occur double patient files. So that data processing becomes ineffective and inefficient. There are several public and employee perception of the administration of health care information system in health center Bayan. This is the author's interest in conducting research on employee perceptions of the application of information systems administration in the improvement of health services in health center Bayan and in this case the author uses qualitative research methods in which a qualitative study that examines the participants with strategies that are interactive and flexible. The qualitative research aimed at understanding social phenomena from the perspective of the participants. The results obtained from this study is an information system that is applied to the health center administration Bayan still using a manual system, which means keep using the computer but not connected to a data network local area network ( LAN) and does not use as a database server. From this study it can be concluded that the health care information system in health center Bayan already well underway although there are some deficiencies in the means of infrastructures and human resources.